The application of authentic assessment in history learning at Don Bosco high school Padang - Ari P Silalahi (International Conferences on Educational, Social Sciences and Technology)
This study aims to describe how teachers in applying authentic assessment in historical learning in accordance with the demands of Curriculum 2013. This research is a qualitative descriptive study. The data collection techniques used are observation, interview, and documentation study. Data were analyzed by data reduction, data presentation, and conclusions. The result of the research shows that: 1) teachers and principals are able to apply authentic assessment in history lessons based on attitude, knowledge, and skill attitudes assessment, 2) real authentic assessment implemented by teacher in the field so that the result of the learner achievement until end of semester) 3) the assessment done by the teacher is not just knowledge but how the teacher understands each developmental characteristics of the learners, 4) by performing an authentic assessment in the learning history of learners have the intellectual ability and academic brilliance, the heirs of the values of nationality and have concern for the problems of life society and nation by conducting an authentic assessment in the learning history of learners having intellectual ability and academic brilliance, the heirs of national values and having concern for the present and future life of society.